The prevalence of poor sleep quality and its association with depression and anxiety scores in patients admitted for cardiovascular disease: A cross-sectional designed study. (1st February 2017) - Matsuda, Risa; Kohno, Takashi; Kohsaka, Shun; Fukuoka, Ryoma; Maekawa, Yuichiro; Sano, Motoaki; Takatsuki, Seiji; Fukuda, Keiichi
Abstract: Background: Poor sleep quality contributes to the development of various cardiovascular conditions. However, its real-world prevalence among cardiovascular inpatients and association with psychological disturbance is unknown. This study aimed to assess the prevalence of poor sleep quality and its association with depression and anxiety in cardiovascular patients, and explored whether sex and cardiovascular comorbidities modified these associations. Methods: A total of 1071 patients hospitalized for a broad spectrum of cardiovascular diseases at a single university hospital were assessed (790 men, mean age 64 ± 14 years). We assessed sleep quality during their index hospitalization period using the Pittsburgh Sleep Quality Index (PSQI); poor sleep quality was defined as PSQI > 5. Depression and anxiety were assessed with the Hospital Anxiety and Depression Scale (HADS). Results: The median PSQI score was 5.0 [3.0–7.0], and 461 inpatients (43%) had poor sleep quality. Multivariate regression analysis adjusting for patient background, medical risk factors, and laboratory data revealed that poor sleep quality was associated with higher HADS subscores for depression (HADS-depression; odds ratio [OR]: 1.09, 95% confidence interval [CI]: 1.03–1.15) and anxiety (HADS-anxiety; OR: 1.17, 95% CI: 1.11–1.24). Poor sleep quality was associated with markedly higher HADS-depression among women than men (p value for interaction: 0.008). The association between poor sleep quality and HADS-anxiety was more significant among patients without coronary artery diseases (p value for interaction: 0.017). Conclusions: Poor sleep quality was highly prevalent and associated with depression and anxiety in cardiovascular patients. These associations may be modified by sex and the presence of coronary artery diseases. Highlights: Poor sleep quality was highly prevalent in patients with cardiovascular diseases. The presence of poor sleep quality was independently associated with depression and anxiety symptoms in patients with cardiovascular diseases. The association between poor sleep quality and depressive or anxiety symptoms was modified by sex and the presence of coronary artery diseases.